1996
DOI: 10.1046/j.1365-313x.1996.09030369.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of putative branchpoint consensus sequences in plant introns reduces splicing efficiency

Abstract: Intron lariat formation between the 5' end of an intron and a branchpoint adenosine is a fundamental aspect of the first step in animal and yeast nuclear pre-mRNA splicing. Despite similarities in intron sequence requirements and the components of splicing, differences exist between the splicing of plant and vertebrate introns. The identification of AU-rich sequences as major functional elements in plant introns and the demonstration that a branchpoint consensus sequence was not required for splicing have led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 0 publications
3
77
0
1
Order By: Relevance
“…6A) is the best candidate for the BPS used in conjunction with the type 3 AG. However, the normally observed distance between the BPS and 3# splice site AG is 18 to 40 nt (Simpson et al, 1996(Simpson et al, , 2002 and therefore larger than the 16 nt between BPS5 and the type 3 AG. The suboptimal placement of the intron IV type 3 AG relative to BPS5 may promote the use of the additional type 1 and type 2 sites.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…6A) is the best candidate for the BPS used in conjunction with the type 3 AG. However, the normally observed distance between the BPS and 3# splice site AG is 18 to 40 nt (Simpson et al, 1996(Simpson et al, , 2002 and therefore larger than the 16 nt between BPS5 and the type 3 AG. The suboptimal placement of the intron IV type 3 AG relative to BPS5 may promote the use of the additional type 1 and type 2 sites.…”
Section: Discussionmentioning
confidence: 87%
“…If multiple AGs lie in close proximity to each other, sequence context can affect selection of the preferred AG (Smith et al, 1993). The position of an upstream branch point sequence (BPS) further influences the selection of the 3# splice site (Simpson et al, 1996). The BPS is defined by the consensus sequence CURAY (most highly conserved underlined) and is generally located 18 to 40 nt upstream of the 3# splice site.…”
Section: Multiple Zmhy2 Transcripts Accumulate In Elm1 and Elm1 Plantsmentioning
confidence: 99%
“…By comparing the sixth intron of the ARF18 alleles, extensive variations, including six SNPs and an 11-bp insertion, were detected in the region upstream of the 3′ splicing site in the nonfunctional sixth intron. In plants, although individual introns exhibit extensive variation around highly conserved dinucleotides (GU and AG) at the 5′ and 3′ splice sites (29), branchpoint sequences (YUNAN consensus) that usually are located 18-40 nt upstream of the 3′ splice site of introns play an important role in splicing efficiency (30). Introns are removed via a two-step cleavage-ligation reaction in which the first step involves cleavage at the 5′ splice site with formation of an intron lariat at the branchpoint (31).…”
Section: Discussion Variation In the Region Upstream Of The 3′ Splicementioning
confidence: 99%
“…Previous reports have shown that Q-rich MRs in ARFs function as activation domains (29). This finding suggests that ARF18 might function as a repressor because it does not possess a Q-rich MR. To confirm our inference, we detected the transcriptional activity of ARF18 by using a protoplast assay system.…”
Section: Incorrect Splicing Of the Sixth Intron Induces Nonfunctionalmentioning
confidence: 88%
“…The intron sequences together with the fragments (>55 bp) from the original 5′- and 3′-exons were isolated from Arabidopsis genomic DNA by PCR and introduced to the plant expression vector pDH515 within an intronless zein gene using the unique Bam HI restriction site [42,43]. For the mutant intron construct generation (with different tRNA types), a two-step PCR-based approach was used.…”
Section: Methodsmentioning
confidence: 99%